Lenalidomide for relapsed or refractory multiple myeloma - S. S. Bessmeltsev1; E. V. Kariagina; L. V. Stelmashenko; G. N. Salogub; E. R. Machulaitene; K. M. Abdulkadyrov; N. A. Kotova; I. I. Kostroma; N. V. Medvedeva; L. I. Krylova; E. Yu. Ilushkina (Онкогематология)
We report the activity of lenalidomide (revlimide – R), lenalidomide plus dexamethasone (Rd), lenalidomide plus bortezomib plus dexamethasone (RVd) in 34 patients with relapsed and refractory myeloma. For patients who received lenalidomide the overall response rate was 70.5 %. 38 % patients achieved very good partial response (VGPR) + complete response (CR). Median overall survival (OS) was 48 months. Lenalidomide may overcome the poor prognostic impact of various factors, particularly elevated beta (2)-microglobulin. Lenalidomide is highly active in elderly patients (> 65 years). Significantly increased OS with a lenalidomide-based induction and lenalidomide maintenance therapy was revealed. The median duration of the overall response without lenalidomide maintenance therapy was 10 months. The median duration of the overall response with lenalidomide maintenance therapy was 20 months (р < 0,05). Median OS with lenalidomide maintenance therapy was not reached. Median OS without lenalidomide maintenance therapy was 36 months (р < 0.05). Side effects were predictable and manageable. The most common adverse events reported were neutropenia (38.3 %) and thrombocytopenia (23.7 %). Serious adverse events were rare.